Pan drug-resistant Salmonella ser. Typhi septicaemia in a child- a case report - Safdar, Nida; Malik, Nasrullah; Nizamuddin, Summiya; Rasool, Attya (Journal of the Pakistan Medical Association, 2023)
Typhoid fever, caused by Salmonella enterica serovar Typhi, is a common cause of febrile illness, especially in lower-middle-income countries. The only known reservoirs of this infection are humans, and it is prevalent in areas with limited availability of clean drinking water and sanitary conditions. Lately, extensively drug-resistant Salmonella ser. Typhi (XDR S. Typhi) has emerged as one of Pakistan’s most challenging public health concerns. Here, we report a case of relapsed typhoid fever in a child, in whom the isolate was found to be resistant to meropenem and azithromycin. Keywords: Salmonella, Antibiotics, typhoid fever, Septicaemia.